2006
DOI: 10.1016/j.jasms.2006.06.026
|View full text |Cite
|
Sign up to set email alerts
|

An analytical strategy for quaternary ammonium neuromuscular blocking agents in a forensic setting using LC-MS/MS on a tandem quadrupole/time-of-flight instrument

Abstract: An analytical strategy is described for analyzing quaternary ammonium neuromuscular blocking agents in a wide variety of biological specimens in a forensic setting. Neuromuscular blocking agents such as succinylcholine, pancuronium, and tubocurarine, often used as paralytic agents during surgery, are occasionally suspected as paralytic poisoning agents involved in suspected homicide and suicide cases. Because suspicion in such cases can develop slowly, the age, nature, and quality of available specimens varies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
41
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 25 publications
3
41
0
Order By: Relevance
“…false-positive results, this special case additionally emphasizes the possible detrimental effects on scientific research: The fact that SMC was recently found in native post-mortem tissues, thus raising the question as to the existence of endogenous SMC, 15,16 could easily have mislead us to consider our preliminary results as supportive of this theory. This is especially true since the previously reported SMC tissue concentrations vary around 50 ng/ mL, 16 which closely resembles our mean serous interference concentration of 55.9 ng/mL SMC eq. Additionally, the discovery of similar physicochemical features of the interference compared to SMC, namely its likewise alkali-labile character, could have been mistaken as a further indication for the existence of native SMC.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…false-positive results, this special case additionally emphasizes the possible detrimental effects on scientific research: The fact that SMC was recently found in native post-mortem tissues, thus raising the question as to the existence of endogenous SMC, 15,16 could easily have mislead us to consider our preliminary results as supportive of this theory. This is especially true since the previously reported SMC tissue concentrations vary around 50 ng/ mL, 16 which closely resembles our mean serous interference concentration of 55.9 ng/mL SMC eq. Additionally, the discovery of similar physicochemical features of the interference compared to SMC, namely its likewise alkali-labile character, could have been mistaken as a further indication for the existence of native SMC.…”
Section: Discussionmentioning
confidence: 74%
“…Apart from the negative implications which an uncritical interpretation of such interference-prone data must have for toxicological case-work, i.e. false-positive results, this special case additionally emphasizes the possible detrimental effects on scientific research: The fact that SMC was recently found in native post-mortem tissues, thus raising the question as to the existence of endogenous SMC, 15,16 could easily have mislead us to consider our preliminary results as supportive of this theory. This is especially true since the previously reported SMC tissue concentrations vary around 50 ng/ mL, 16 which closely resembles our mean serous interference concentration of 55.9 ng/mL SMC eq.…”
Section: Discussionmentioning
confidence: 81%
“…Comparably larger difficulties were met during the sensible modeling of the elimination processes: it is undisputed that for both SUX and SMC, peripheral elimination is possible or even probable [e.g., considering the observed instability of these substances in tissues (9,23)]. However, the extent of this elimination is totally unknown.…”
Section: Discussionmentioning
confidence: 99%
“…With SMC as a marker, the time frame for possible detection of an SUX application has ultimately been extended from a few minutes to [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] h, yet it is conceivable that forensic casework in alleged SUX intoxications remains critical. In contrast to the majority of substances subjected to a CYP-P450-based metabolism, degradation of SUX and SMC is independent of an intact cardiovascular system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation